Essays on technology and exporting by Indian firms in a globalised World - Yang, Shubin (2017)
This thesis consists of three self-contained studies on technology and exporting of Indian firms in the post-liberalization era. In Chapter 1, we describe the background of Indian economic reforms, provide a general introduction and motivation, and give a brief outline of the thesis. Chapter 2 introduces the data, the variables used in the empirical estimations of the followed chapters, the sample selection steps, and presents some descriptive statistics. Chapter 3 studies regional and national productivity convergence among manufacturing firms in India, using a panel data over the period 1999 to 2010. We find that firms are converging to both their national and regional frontier, and they converge faster to their national frontier than to the regional frontier. We pay attention to the effects of globalisation on the speed of convergence, and find that both export and outward FDI facilitates firms’ productivity growth but slows down the convergence speed. Chapter 4 investigates the role of financing sources on the joint decision to invest in technology and to export, for both manufacturing and service firms in India. We find that firms with higher internal financing are more likely to engage in technology investment and exporting, and this pattern is consistent between manufacturing and service firms. The effects of external financing sources are not statistically significant for manufacturing firms, but show a significant and positive effect on service firms’ decision to undertake technology investments. We further investigate the impact of financial reforms in India for the manufacturing firms, and find a weak effect of the financial reforms in reducing the effects of internal sources on exporting. Chapter 5 summarises the main findings and implications of the thesis, and provides a short discussion of future research directions.